2023
DOI: 10.3390/molecules28196816
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Research Progress on Polysaccharides from Fungal Traditional Chinese Medicine

Chenxi Bai,
Fazhi Su,
Wensen Zhang
et al.

Abstract: Traditional Chinese medicine (TCM) is a class of natural drugs with multiple components and significant therapeutic effects through multiple targets. It also originates from a wide range of sources containing plants, animals and minerals, and among them, plant-based Chinese medicine also includes fungi. Fungal traditional Chinese medicine is a medicinal resource with a long history and widespread application in China. Accumulating evidence confirms that polysaccharide is the main pharmacodynamic material on wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…In recent years, studies have shown that the extracts of medicinal plant active ingredients, including Chinese herbal polysaccharides, have been playing a positive role in livestock production and disease prevention and treatment (12). Chinese herbal polysaccharide can play a variety of biological functions (36,37), such as antiinflammatory (38), anti-tumor (39), antioxidant, lowering blood sugar, lowering blood lipids (40), immune regulation (41), and regulating intestinal flora (42), etc. Chen et al found that the basal diet supplemented with 1,000 mg/kg Lonicera fulvotomentosa extract could significantly increase the final weight of weaned piglets and the diversity and richness of intestinal flora in the jejunum and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have shown that the extracts of medicinal plant active ingredients, including Chinese herbal polysaccharides, have been playing a positive role in livestock production and disease prevention and treatment (12). Chinese herbal polysaccharide can play a variety of biological functions (36,37), such as antiinflammatory (38), anti-tumor (39), antioxidant, lowering blood sugar, lowering blood lipids (40), immune regulation (41), and regulating intestinal flora (42), etc. Chen et al found that the basal diet supplemented with 1,000 mg/kg Lonicera fulvotomentosa extract could significantly increase the final weight of weaned piglets and the diversity and richness of intestinal flora in the jejunum and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptogens are substances that help the body adapt to stressors and enhance their performance [16][17][18] by promoting balance and resilience without causing significant side effects. Fungi, like Ganoderma lucidum (Lingzhi), Cordyceps sinensis (Dong Chong Xia Cao), Lentinula edodes (Shiitake), Auricularia auricula-judae (Wood Ear), Trametes versicolor (Yunzhi), and Tremella fuciformis (Silver Ear), with their high contents of bioactive compounds, such as polysaccharides [19], triterpenoids [20], flavonoids and phenolic compounds [21], have been utilized in TCM for centuries to bolster the body's defenses, enhance vitality, and restore equilibrium, with beneficial effects on the aging process by supporting longevity and vitality [22,23].…”
Section: Introductionmentioning
confidence: 99%